2013
DOI: 10.5935/paet.v6.n2.09
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of essential oil and vegetable extracts ofSalvia officinalisL. in the control of rot sclerotinia in lettuce

Abstract: In the search of alternative methods for disease control in plants, the essential oil and vegetal extracts of Salvia officinalis appear as an option. In this study, it was evaluated in vitro and in vivo the effect of the essential oil and plant extracts (hydroethanol, ethanol and infusion) of Salvia officinalis with potential antifungal activity against the pathogen Sclerotinia sclerotiorum (Lib.) de Bary. The essential oil was tested in the concentrations of 0.01, 0.05, 0.1, 0.15 and 0.2%, and the extracts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The first step of this study was to check whether the treatment has any fungicide effect and interfere with the growth of the fungi. Contrary to observed with Azadirachta indica, Zingiber officinale or Salvia officinalis extracts against Sclerotinia (Ojaghian et al 2014;Pansera et al 2008), or other plant pathogens (Dorantes et al 2000), the mix extract of M. tenuiflora and Q. robur is unable to inhibit the mycelial growth in vitro or the germination of sclerotia. These results suggest that this extract is not toxic to the fungi, and its possible mode of action is not related to fungicidal or fungistatic effects.…”
Section: Discussionmentioning
confidence: 73%
“…The first step of this study was to check whether the treatment has any fungicide effect and interfere with the growth of the fungi. Contrary to observed with Azadirachta indica, Zingiber officinale or Salvia officinalis extracts against Sclerotinia (Ojaghian et al 2014;Pansera et al 2008), or other plant pathogens (Dorantes et al 2000), the mix extract of M. tenuiflora and Q. robur is unable to inhibit the mycelial growth in vitro or the germination of sclerotia. These results suggest that this extract is not toxic to the fungi, and its possible mode of action is not related to fungicidal or fungistatic effects.…”
Section: Discussionmentioning
confidence: 73%
“…Volatility of active molecules from sage EOs benefits fumigating applications against soil-borne [120] and storage pathogens [146]. S. officinalis EO proved to be a potential alternative method to conventional fungicides for the control of Sclerotinia rot in lettuce [78].…”
Section: Sage Essential Oilsmentioning
confidence: 99%
“…this result agree with (Al-Taisan et al, 2014) they found that, cinnamon oil produced the best result for reducing the sclerotinia rot disease incidence that produced 75% survival bean plants when compared with controls. essential oil of salvia officinalis reduced the sclerotinia rot disease of lettuce from 100% in control to 20% (Pansera et al, 2013). treating cucumber plants with olive oil, clove oil, nigella oil and rocket oil significantly reduced the percentage of powdery mildew incidence and severity compared with the control treatment.…”
Section: Discussionmentioning
confidence: 91%